Chronic airway obstruction in a population-based adult asthma cohort: Prevalence, incidence and prognostic factors. (May 2018) - Backman, Helena; Jansson, Sven-Arne; Stridsman, Caroline; Muellerova, Hana; Wurst, Keele; Hedman, Linnea; Lindberg, Anne; Rönmark, Eva
Abstract: Background: Asthma and COPD may overlap (ACO) but information about incidence and risk factors are lacking. This study aimed to estimate prevalence, incidence and risk factors of chronic airway obstruction (CAO) in a population-based adult asthma cohort. Methods: During 1986–2001 a large population-based asthma cohort was identified (n = 2055, 19-72y). Subsamples have participated in clinical follow-ups during the subsequent years. The entire cohort was invited to a clinical follow-up including interview, spirometry, and blood sampling in 2012–2014 when n = 983 subjects performed adequate spirometry. CAO was defined as post-bronchodilator FEV1 /FVC<0.7. Results: At study entry, asthmatics with prevalent CAO (11.4%) reported more respiratory symptoms, asthma medication use, and ischemic heart disease than asthmatics without CAO (asthma only). Subjects who developed CAO during follow-up (17.6%; incidence rate of 16/1000/year) had a more rapid FEV1 decline and higher levels of neutrophils than asthma only. Smoking, older age and male sex were independently associated with increased risk for both prevalent and incident CAO, while obesity had a protective effect. Conclusions: In this prospective adult asthma cohort, the majority did not develop CAO. Smoking, older age and male sex were risk factors for prevalent and incident CAO, similar to risk factors described for COPD in the general population. Highlights: The majority of asthmatics do not develop CAO. The main risk factors for the development of CAO among asthmatics are smoking, older age and male sex. Risk factors for CAO among asthmatics are similar as for COPD in the general population.